China's climate change policy: Central–local governmental interaction. (3rd February 2020) - Zhang, Yunhan; Orbie, Jan; Delputte, Sarah
Abstract: It is indisputable that China has been a major actor in climate change. This raises the question: of which lens is most appropriate to gain an understanding of the recent changes in China's domestic climate change policy? Although there is insufficient attention paid to political science accounts of central–local relations in climate governance, this article aims to contribute to the theoretical research on Chinese climate change policy by developing and applying a theoretical framework. Using this novel theoretical framework based on systems theory, this article analyses the complex allocation of power and incentives between the central and local governments. Methodologically, this research is based on expert interviews with relevant officials, negotiators, scholars, climate nongovernmental organizations, and emitter companies. Our analysis reveals that this evolution has been a nonlinear process that has been substantially influenced by central–local governmental interactions. Specifically, we find two trial‐and‐error processes in the evolution of China's climate change policy. We conclude with some reflections on the wider implications of this recentralization trend for the long‐term sustainability of China's climate change policies.